The Ki-67 Proliferation Index-Related Nomogram to Predict the Response of First-Line Tyrosine Kinase Inhibitors or Chemotherapy in Non-small Cell Lung Cancer Patients With Epidermal Growth Factor Receptor-Mutant Status - Gu, Weiguo; Hu, Mingbin; Xu, Linlin; Ren, Yuanhui; Mei, Jinhong; Wang, Weijia; Wang, Chunliang (Frontiers in Medicine, 2021)
Background: The correlation between Ki67 and EGFR- or KRAS-mutant status in advanced or postoperative-recurrent non-small cell lung cancer (NSCLC) has less studies reported, and the prognostic role of Ki67 with first-line EGFR-TKIs or chemotherapy remains controversial. Methods: A total of 295 patients were tested for EGFR-mutant status in advanced or postoperative-recurrent NSCLC and received first-line EGFR-TKIs or chemotherapy treatment. Ki67 expression was retrospectively analysed by immunohistochemistry. The Kaplan-Meier method was used to calculate survival rates. The multivariate Cox proportional hazards model was used to generate a nomogram. The established nomogram was validated using the calibration plots. Results: The expression of Ki67 was divided into low (<60%, n=186) and high (≥60%, n=109) groups, based on the receiver operating characteristic curve. The expression levels of Ki67 were higher in patients with KRAS-mutation or EGFR-wildtype group than in those with KRAS wildtype or EGFR-mutation. The low Ki67 group of median OS was significantly longer than high Ki67 group, no matter in all NSCLC, EGFR-mutation, EGFR-wildtype, KRAS-mutant status, EGFR-TKIs or chemotherapy of patients(P<0.05). Subgroup analysed showed that the KRAS-wildtype or EGFR-mutation combines with low Ki67 expression group had a longest median OS than KRAS-mutation or EGFR-wildtype combines with Ki67 high expression group(P<0.05). The multivariate Cox analysis identified age, serum LDH, serum Cyfra211, EGFR-mutation and Ki67 as independent prognostic factors in the training cohort, and the nomogram was developed based on these covariates. The calibration curve for predicting the 12-, 24-, and 30-month OS showed an optimal agreement between the predicted and actual observed outcomes. Conclusions: The establishment of a nomogram based on Ki67 expression can well predict the efficacy of first-line therapy in NSCLC patients with EGFR- or KRAS-mutant status, high expression of Ki67 correlated with poor prognosis.